On the Statistical Properties of Nakagami-Hoyt Vehicle-to-Vehicle Fading Channel under Nonisotropic Scattering - Muhammad Imran Akram; Asrar U. H. Sheikh (International Journal of Antennas and Propagation)
This paper presents the statistical properties of the vehicle-to-vehicle Nakagami-Hoyt (Nakagami-q) channel model under non-isotropic condition. The spatial time correlation function (STCF), the power spectral density (PSD), squared time autocorrelation function (SQCF), level crossing rate (LCR), and the average duration of Fade (ADF) of the Nakagami-Hoyt channel have been derived under the assumption that both the transmitter and receiver are nonstationary having nonomnidirectional antennas. A simulator that uses the inverse-fast-fourier-transform- (IFFT-) based computation method is designed for this model. The simulator and analytical results are compared.